Bidentate Phosphine–Phosphoramidite Ligands of the BettiPhos Family for Rh‐Catalyzed Asymmetric Hydrogenation. Issue 28 (26th July 2017) - Schmitz, Christian; Holthusen, Katharina; Leitner, Walter; Franciò, Giancarlo
Abstract : Phosphine–phosphoramidites comprising a stereogenic phosphorus atom at the phosphoramidite moiety and a Betti base as chiral backbone have been synthesized. Individual diastereomers have been benchmarked as ligands in the Rh‐catalyzed asymmetric hydrogenation of dimethyl itaconate to study the interplay of the different elements of chirality. The privileged diastereomer was applied to Rh‐catalyzed asymmetric hydrogenation of several functionalized olefins, leading to high enantioselectivities between 91 and 97 % ee, which confirms the effectiveness of the BettiPhos ligand family in asymmetric catalysis. Abstract : Phosphine–phosphoramidite BettiPhosO ligands comprising a stereogenic phosphorus atom at the phosphoramidite moiety and a Betti base as chiral backbone have been used in the Rh‐catalyzed hydrogenation of functionalized olefins, leading to high enantioselectivities between 91 and 97 % ee confirming the effectiveness of the Betti base as valuable synthon for chiral phosphorus ligands.